MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE DEMONSTRASI PADA MATA PELAJARAN IPA DI KELAS IV SD ISLAM TOMPOKERSAN LUMAJANG - Munif, Abdul (Jurnal Analisis Pendidikan Sosial, 2025)
The problems studied in this study are: "How to improve the science learning achievement of fourth grade students in the material of classifying animals based on the type of food in Islamic Elementary School Tompokersan Lumajang by applying the demonstration method?" This study aims to improve student learning outcomes in science subject matter by using the demonstration method for fourth grade students of Islamic Elementary School Tompokersan Lumajang. This type of research is classroom action research (CAR), with 28 students as the subject of Class IV Islamic Elementary School Tompokersan Lumajan. This type of research is classroom action research which is carried out in 2 cycles, each cycle consisting of planning, action, observation, and reflection stages. The data obtained in the study are student learning outcomes taken from the written test scores at the end of the cycle. The indicator of success in this study is an increase in student learning outcomes seen from the increase in class averages and the percentage of complete learning reaching 85.71% of the number of fourth grade students at Islamic Elementary School Tompokersan Lumajang. Based on the observations of the science learning process using the demonstration method learning model in fourth grade students of SD Islam Tompokersan Lumajang, it can take place in a conducive, interactive, dynamic, open, interesting, and fun atmosphere, thus encouraging students to be active in learning, enthusiastic about participating in learning, and establish good communication with classmates while studying. The science learning outcomes of fourth grade students of Islamic Elementary School Tompokersan Lumajang seen from the class average value increased, namely in the pre-cycle of 39.29%, the first cycle of 57.14%, and the second cycle of 85.71%. Thus, the application of the demonstration method learning model can improve science learning outcomes for fourth grade students at Islamic Elementary School Tompokersan Lumajang